The Production of Space and Resilience Strategies in Sanur Traditional Village: A Case Study in Denpasar's Tourism Context - Wijaatmaja, Arya Bagus Mahadwijati; Putra, I Dewa Gede Agung Diasana; Dwijendra, Ngakan Ketut Acwin; Yudantini, Ni Made (Universitas Ibn Khaldun Bogor, 2025)
This study examines the resilience and adaptation of the production of space in Sanur Traditional Village, Denpasar, amidst the pressures of tourism development. As tourism has become a key economic sector in Bali, traditional villages like Sanur face significant challenges in maintaining their socio-cultural identity while adapting to rapid changes. Using Henri Lefebvre's theory of the production of space as a conceptual framework, this research explores how Sanur negotiates between preserving traditional spatial practices and accommodating tourism demands. The study employs a qualitative case study approach, utilizing interviews, observations, and document analysis to investigate the dynamics of the production of space in Sanur. The research questions focus on: 1) How tourism development has influenced the production of space in Sanur; 2) Challenges To Traditional Spatial Planning; and 3) What resilience and adaptation strategies have been employed. The novelty of this research lies in its multidimensional approach to understanding spatial resilience in the context of a traditional Balinese village, integrating concepts of the production of space, cultural resilience, and tourism development. Preliminary findings suggest a complex interplay between traditional spatial concepts (e.g., Tri Hita Karana philosophy) and modern tourism-driven spatial transformations. The village demonstrates resilience through innovative spatial practices that balance cultural preservation with economic opportunities. This research contributes to the broader understanding of spatial resilience in traditional communities facing modernization pressures and offers insights for sustainable tourism development policies.